2021
DOI: 10.31234/osf.io/g7tu6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility of computerized positive mental imagery training as a treatment adjunct in inpatient mental health settings: a randomized controlled trial

Abstract: Background: Positive affect and anhedonia are important but challenging targets for mental health treatments. Previous research indicates the potential of a computerized cognitive training paradigm involving generation of positive mental imagery, here termed positive mental imagery training (PMIT), to increase positive affect and reduce anhedonia. Aims: Our main aim was to investigate feasibility of PMIT as a positive affect-focussed transdiagnostic adjunct to treatment as usual (TAU) for patients in inpatient… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Supporting the cognitive reserve hypothesis, instructing participants to imagine a future event vividly led to a significant reduction in delay discounting, impulsive behavior and substance consumption (Peters and Büchel, 2010;Forster et al, 2021). Similar effects have been found for internalizing behavior such as depression and anxiety (Jing et al, 2016;Westermann et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Supporting the cognitive reserve hypothesis, instructing participants to imagine a future event vividly led to a significant reduction in delay discounting, impulsive behavior and substance consumption (Peters and Büchel, 2010;Forster et al, 2021). Similar effects have been found for internalizing behavior such as depression and anxiety (Jing et al, 2016;Westermann et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
“…Experimental studies confirmed these findings and suggest that the observed link may provide possible implications for clinical practice (e.g., Renner et al, 2021). For example, training or instructing EFT about positive future events did not only elicit positive affect in the here-and-now, but also increased anticipated pleasure and the intention to perform related activities in healthy controls (Hallford et al, 2020a;Westermann et al, 2021;Hallford et al, 2022). Beyond EFT, there is some, albeit considerably less evidence, that also other facets of future-oriented cognition such as delay discounting, planning and prospective memory may be altered in subjects showing internalizing symptoms (Miloyan et al, 2014;McFarland and Vasterling, 2018; for a review).…”
Section: Internalizing Problems and Future-oriented Cognitionmentioning
confidence: 66%
“…All intervention arms were variants of imagery CBM, adapted from previous experimental (e.g., Holmes et al, 2009) and clinical (e.g., Westermann et al, 2021) CBMv1. CBMv1 started with an initial introductory session comprising an extended introduction to mental imagery followed by 20 training scenarios, as per a recent study (Westermann et al, 2021). The first two training weeks then included four sessions with 40 scenarios each, and the final two weeks included two sessions of 40 scenarios.…”
Section: Intervention Arms: Imagery Cognitive Bias Modification (Imag...mentioning
confidence: 99%
“…Participants then completed the sets of training scenarios. In between each set of scenarios, participants were shown a tabular display of their minimum, maximum, and average vividness ratings for all sets completed so far that session, and encouraged to reflect on the scores, what had helped or hindered them in generating vivid imagery, and how they could try to improve on this in the subsequent set (adapted from Westermann et al, 2021).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation